58 Smokers Have Worse Rotator Cuff Teartendon Degeneration And Apoptosis. (5th September 2014) - Lundgreen, Kirsten; Lian, Øystein Bjerkestrand; Scott, Alex; Fearon, Angela; Engebretsen, Lars
Abstract : Introduction: Human studies indicate smokers to be more prone to rotator cuff tears and to present inferior results following rotator cuff repair compared to non-smokers [Baumgarten, 2010; Carbone, 2012; Kane, 2006; Kukkonen, 2012; Mallon, 2004]. We wished to assess the effect of smoking on the histopathology of supraspinatus tendinopathy. Methods: Supraspinatus tendon samples of 10 smokers and 15 non-smokers with full-thickness tears were harvested arthroscopically during rotator cuff repair. The severity of tendon histopathology including apoptosis, cellularity and proliferation was evaluated. Immunohistochemistry was used to assess the density of apoptotic cells (activated caspase-3; Asp175), proliferation (Ki67) and p53 (M7001)). Tendon degeneration was evaluated on tissue sections stained with H&E and Alcian blue according to a revised version of the modified Bonar score [Fearon, 2013]. Results: The smokers were significantly younger (p = 0.01) and presented tears with a longer symptom duration than non-smokers (p < 0.05). The smokers' tendons were characterised by more advanced degenerative changes (Bonar score, 13.5 [interquartile range, 1.4] v 9 [interquartile range, 3]; p < 0.001). These were accompanied by increased density of apoptotic cells (0.108 [SE, 0.038] v 0.0107 [SE, 0.007]; p = 0.024) (Figure 1 ), reduced tenocyte density (p = 0.019) and increased proliferative activity compared to torn supraspinatus tendons of non-smokers (p < 0.0001). Discussion: Smoking is associated with early-onset tendon degeneration. Pronounced degenerative changes with reduced cell density and increased apoptotic cell death in smokers' tendons may be associated with reduced tendon healing capacity. We recommend smoking to be controlled for in clinical studies on tendinopathy. References: Baumgarten KM et al . Clin Orthop Relat Res 2010;468(6):1534–1541 Carbone S et al . J Shoulder Elbow Surg 2012;21(1):56–60 Fearon A et al . J Sci Med Sport in press, online 8 August, 2013. doi:10.1016/j.jsams.2013.07.008 Kane SM et al . Orthopedics 2006;29(4):363–366 Kukkonen J et al . Scand J Med Sci Sports 2012;24:400–403 Mallon WJ et al . J Shoulder Elbow Surg 2004;13(2):129–132